Police Leadership in Operational Function (Case Study at the Bogor Police) - Silfia Sukma Rosa; Chairul Muriman Setyabudi; Sutrisno Sutrisno (Budapest International Research and Critics University, 2022)
The female police profession is a job that is carried out as a main activity to produce performance and which relies on a skill. Meanwhile, professionalism is a female police officer's commitment to her profession, as well as a 'spirit' or spirit, perspective, method, and/or practice those traces and describes a series of characteristics of the profession concerned. This commitment is shown by his pride as a professional, continuous efforts to develop professional abilities. There are many opinions about the elements that can be considered as part of the characteristics that build the professionalism of a profession. One opinion states that a profession is characterized by, among other things, certain specifications relating to: education and training, intellectual or theoretical expertise/competence as well as technical, organizational, discipline and code of ethics, as well as commitment to altruistic services (public services). This study has the intent and purpose to analyze how the policewomen who serve in the Bogor Police as leaders in the operational field and to improve the professionalism and leadership of the Police for the advancement of the Police. The method that the author uses in reviewing and discussing research problems is the descriptive analysis method. The results of the study revealed that the views of members of the function unit towards female police officers who served in the operational function of the female police leadership at the Bogor Police were based on the readiness of female police officers who had high productivity and performance, namely those who had a desire to provide excellent service to the community. In order to carry out their duties and functions, the Women's Police is a service provider to the public. In the current era of globalization, it is deemed necessary to properly place female police officers. This is very important to do so that the provision of excellent service to the community can be realized. This excellent service is intended so that time, energy, and budget are not wasted because of the services of female police officers.